Enhance of the polystyrene based plastic scintillator radiation hardness; using fluorine-derivatives of 3-hydroxyflavone - Gurkalenko, Yu.A.; Zhmurin, P.M.; Pereymak, V.M.; Yelisieiev, D.A.; Yelisieieva, O.V. (Functional Materials, 2018)
New fluorine-derivatives of 3-hydroxyflavone (3HF) are synthesized. Their spectral luminescent properties are investigated. A range of plastic scintillators (PS), which contain fluorine-derivatives of 3-hydroxyflavone as the activation dopant, is obtained. Influence of replace of hydrogen atoms with fluorine atoms in 3-HF molecules on the PS radiation hardness is studies.